An attempt to revitalize social dialogue and national industrial relations systems in some of the CEECs” – lesson learnt and best practices in the way out of the crisis - Ildikó, Képesné Szabó; Balázs, Rossu (Pécsi Munkajogi Közlemények, 2023)